The warm temperature acclimation protein (Wap65) has an important role in the inflammatory response of turbot (scophthalmus maximus) - Díaz-Rosales, Patricia; Pereiro, Patricia; Figueras Huerta, Antonio; Novoa, Beatriz; Dios, S. (Fish & Shellfish Immunology, 2014)
13 páginas, 10 figuras, 2 tablas.-- Pre-print Wap65 is a molecule similar to the mammalian hemopexin that is a serum glycoprotein produced mainly by the liver with high affinity to heme. Its primary role is participating in iron metabolism scavenging heme that is released into the plasma and transporting it to the liver. It has been reported an important role of hemopexin in the inflammation as an acute-phase protein and its production is up-regulated by pro-inflammatory cytokines. There are also some evidences suggesting this immune-induction in fish Wap65 genes. Most teleost species presents two Wap65 genes but their physiological functions have not been completely elucidated; in fact, the transcriptional patterns of Wap65 genes to stimulatory treatments are variable and contradictory. In the present study two Wap65 genes, Wap65-1 and Wap65-2, have been characterized for the first time in turbot (Scophthalmus maximus). Their constitutive expression and differential modulation by thermal treatments, immune challenges (bacterial and viral), as well as iron supplementation, have been investigated. Both genes were mainly expressed in liver, but they were detected in all tested tissues. Whereas Wap65-1 and Wap65-2 were up-regulated by temperature rise and bacterial challenge, VHSV infection inhibited the expression of both genes. Moreover, iron-dextran administration induced only the overexpression of Wap65-1. Interestingly, these induction were observed in head kidney buy not in liver. The effect of Wap65 protein purified from turbot serum by hemin-agarose affinity chromatography was also studied to demonstrate a possible anti-inflammatory role, analyzing its inhibitory effect on leucocytes migration induced by zymosan injection to the peritoneal cavity We wish to thank the Spanish Ministerio de Ciencia e Innovación for funding through projects CSD2007-00002 “Aquagenomics” of the Consolider-Ingenio 2010 program and AGL2011-28921-CO3 “IMTRA-VAC”. P. Diaz-Rosales and P. Pereiro wish to thank the Spanish National ...